The role of targeted therapy and immune therapy in the management of non-small cell lung cancer brain metastases - Billena, Cole; Lobbous, Mina; Cordova, Christine A.; Peereboom, David; Torres-Trejo, Alejandro; Chan, Timothy; Murphy, Erin; Chao, Samuel T.; Suh, John; Yu, Jennifer S. (Frontiers in Oncology, 2023)
Brain metastases are a significant source of morbidity and mortality in patients with non-small cell lung cancer. Historically, surgery and radiation therapy have been essential to maintaining disease control within the central nervous system due to poorly penetrant conventional chemotherapy. With the advent of targeted therapy against actionable driver mutations, there is potential to control limited and asymptomatic intracranial disease and delay local therapy until progression. In this review paper, intracranial response rates and clinical outcomes to biological and immune therapies are summarized from the literature and appraised to assist clinical decision making and identify areas for further research